Digital Diplomacy and Disinformation: Reshaping Global Public Opinion - Muhammad Arsal Latif; Dr. Samina Rooh; Muhammad Farooq Malik; Abdul Samad (Dialogue Social Science Review (DSSR), 2025)
Digital diplomacy has revolutionized global communication by leveraging social media, artificial intelligence (AI), and real-time engagement, yet it simultaneously amplifies the risks of disinformation, reshaping public opinion in destabilizing ways. This paper examines the dual-edged nature of digital diplomacy, analysing how states and non-state actors exploit platforms like Twitter, Facebook, and TikTok to foster connectivity while spreading disinformation. Through historical precedents—from Cold War propaganda to AI-driven deepfakes—the study underscores disinformation’s evolution into a tool of hybrid warfare, eroding trust in institutions and polarizing societies. Case studies of Russian election interference, Chinese influence operations, and domestic disinformation crises (e.g., the 2020 U.S. Capitol riot) highlight the transnational and psychological impacts of manipulated narratives. The paper argues that combating disinformation requires interdisciplinary strategies, including international cooperation (e.g., the EU’s Digital Services Act), algorithmic transparency, and media literacy initiatives. Recommendations emphasize ethical AI governance, public-private partnerships, and culturally sensitive diplomacy to balance technological innovation with accountability. By integrating these approaches, policymakers can mitigate disinformation’s threats while harnessing digital diplomacy’s potential to foster global stability. The findings stress the urgency of safeguarding truth and equity in an increasingly interconnected yet fragmented information landscape.